Lateral performance of traditional Chinese timber frames: Experiments and analytical model. (1st May 2019) - Xie, Qifang; Zhang, Lipeng; Wang, Long; Zhou, Weijian; Zhou, Tiegang
Highlights: Three single-span TCTF with different column heights were cyclically loaded. With increase of vertical loads, TCTF stiffness increase in initial shift stage. An analytical model was established to analysis lateral behavior of SHF and SSF. Effects of vertical loads and column heights on both SHF and SSF were evaluated. Abstract: This article presents test results of the lateral behavior of traditional Chinese timber frames (TCTF). Three 1/3.52-scaled single-span TCTF specimens, with different column heights and vertical loads application, were subjected to low-cyclic reversed loading tests. The force-rotation hysteretic and envelop curves of these specimens evidently indicate that both vertical loads and column heights have significant effects on the lateral performance of the TCTF. With the increase of vertical loads, specimens' stiffness increase at the initial lateral shift stage and then decrease when larger displacement occurs. An analytical model was established based on the theory of beam-columns. Good consistency between analytical predictions and test results are obtained. The analytical model is well qualified for analysis of the two types of timber frames, one is the SHF (frame with semi-rigid mortise-tenon joints and hinged column-foot joints), another is the SSF (frame with semi-rigid mortise-tenon joints and semi-rigid column-foot joints). Parametric studies were carried out on the SHF and SSF using the established analytical model to further reveal the effects of vertical loads and column heights on the lateral resistance of the TCTF.